METODE KISAH PENDIDIKAN ANAK USIA DINI DALAM HADITS NABI - Bahrul Ulum (Ta'allum: Jurnal Pendidikan Islam, 2020)
This paper aims to study the storytelling method for early childhood education in the Hadith of the Prophet Muhammad r, where many stories are told by the Prophet which contain educational values. Prophet Muhammad as a great educator realizes that the storytelling method is very effective in instilling faith and character building in children's souls, because in the storytelling method there is an attraction that can touch the souls of listeners/students as if he lives in the story and become one of the actors. The story method in Islamic education has functions and tasks that are not found in other educational methods, it is very effective for attracting the children’s attention and stimulating their brains well, and the story in the Hadith Al-Shareef has features that impact on children's psychology and education which are very strong, clear, and long-term. Therefore, The Prophet Muhammad is the most powerfull model for us in educating our children.